Planning, implementation, and scientific goals of the Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC4RS) field mission. Issue 9 (4th May 2016) - Toon, Owen B.; Maring, Hal; Dibb, Jack; Ferrare, Richard; Jacob, Daniel J.; Jensen, Eric J.; Luo, Z. Johnny; Mace, Gerald G.; Pan, Laura L.; Pfister, Lenny; Rosenlof, Karen H.; Redemann, Jens; et al.
Abstract: The Studies of Emissions and Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC 4 RS) field mission based at Ellington Field, Texas, during August and September 2013 employed the most comprehensive airborne payload to date to investigate atmospheric composition over North America. The NASA ER‐2, DC‐8, and SPEC Inc. Learjet flew 57 science flights from the surface to 20 km. The ER‐2 employed seven remote sensing instruments as a satellite surrogate and eight in situ instruments. The DC‐8 employed 23 in situ and five remote sensing instruments for radiation, chemistry, and microphysics. The Learjet used 11 instruments to explore cloud microphysics. SEAC 4 RS launched numerous balloons, augmented AErosol RObotic NETwork, and collaborated with many existing ground measurement sites. Flights investigating convection included close coordination of all three aircraft. Coordinated DC‐8 and ER‐2 flights investigated the optical properties of aerosols, the influence of aerosols on clouds, and the performance of new instruments for satellite measurements of clouds and aerosols. ER‐2 sorties sampled stratospheric injections of water vapor and other chemicals by local and distant convection. DC‐8 flights studied seasonally evolving chemistry in the Southeastern U.S., atmospheric chemistry with lower emissions of NO x and SO2 than in previous decades, isoprene chemistry under high and low NO x conditions at different locations, organic aerosols, air pollution near Houston and in petroleum fields, smoke from wildfires in western forests and from agricultural fires in the Mississippi Valley, and the ways in which the chemistry in the boundary layer and the upper troposphere were influenced by vertical transport in convective clouds. Key Points: The SEAC4RS field mission was based near Houston, Texas during August and September of 2013 The paper overviews the mission to aid those interested in this data set to understand its context The data can be accessed athttp://www‐air.larc.nasa.gov/cgi‐bin/ArcView/seac4rs